Reproductive interference among spider mites : using behaviour and life-history effects to predict eco-evolutionary consequences - Clemente, Salomé Gomes (2019)
Tese de doutoramento, Biodiversidade Genética e Evolução, Universidade de Lisboa, Faculdade de Ciências, 2017